Islamic Law Analysis of Chemical Castration Punishments Post The Decision of Mojokerto State Court No. 69/PID.SUS/2019/PN MJK - Mgs M Hanief Fathurrahman; Muhammad Romli (Al-Mada: Jurnal Agama, Sosial, dan Budaya, 2023)
This research aims to determine the judges' views and basis for deciding the castration chemical sentence in the Mojokerto District Court and to know the review of Islamic Law on the castration chemical decision in the Mojokerto District Court. The research is included in the category of qualitative research based on library research using secondary data sources and descriptive-analytical approaches. The data sources of this study were classified into three parts, namely, primary, secondary, and tertiary legal materials. In comparison, the data analysis in this study uses the deductive method. The conclusions of this research result explain that First, the Panel of judges gave a legal assessment of the Defendant that he had admitted his actions included the Act against the Law, "intentionally committing violence forcing the child to have intercourse with him or with others" as evidenced by the testimony of witnesses under oath, the results of the post mortem and evidence and did the same thing nine times so that the castration chemical punished it. Second, Islamic Law considers that chemical castration is included in the jarimah ta'zir. Because jarimah ta'zir does not yet have provisions from syara' and there is no minimum or maximum limit, the determination of the sentence is the right of the ruler (leader or Judge). Penelitian ini bertujuan untuk mengetahui pandangan hakim dan dasar dalam memutuskan hukuman kebiri kimia di Pengadilan Negeri Mojokerto dan untuk mengetahui tinjauan Hukum Islam terhadap putusan kebiri kimia di Pengadilan Negeri Mojokerto. Penelitian ini termasuk dalam kategori penelitian kualitatif berdasarkan penelitian kepustakaan dengan menggunakan sumber data sekunder dan pendekatan deskriptif-analitik. Sumber data penelitian ini diklasifikasikan menjadi tiga bagian, yaitu data primer, sekunder, dan tersier. Adapun analisis data dalam penelitian ini menggunakan metode deduktif. Kesimpulan dari hasil penelitian ini menjelaskan bahwa; Pertama, Majelis Hakim memberikan penilaian hukum terhadap Terdakwa yang mengakui perbuatannya termasuk Perbuatan melawan Hukum, “sengaja melakukan kekerasan memaksa anak melakukan persetubuhan dengan dirinya atau dengan orang lain” dibuktikan dengan keterangan saksi di bawah sumpah, hasil visum dan barang bukti serta melakukan hal yang sama sebanyak sembilan kali sehingga hukuman kebiri kimia itu. Kedua, Hukum Islam memandang bahwa kebiri kimia termasuk dalam jarimah ta'zir. Karena jarimah ta'zir belum ada ketentuan dari syara' dan belum ada batas minimal atau maksimal, maka penentuan hukuman adalah hak penguasa atau Hakim.